Disparitas Pemidanaan pada Perkara Tindak Pidana Perdagangan Orang - Intan Nurina Seftiniara (Universitas Bandar Lampung (UBL), 2017)
Trafficking in persons is already happening for a long time, the oldest written evidence found indicates that this practice has been going on since the sixth century on Roman territory. Today, people trafficking is dominated by women as victims for the purpose of prostitution. Trafficking is happening in the province of Lampung. Lampung not be the locus delicti. Lampung is sending area. Bandar Lampung in cases of trafficking between 2009 and 2012 with the same charges.problems in the writing of this first study, Why happened disparity in the criminal case of trafficking in persons (Trafficking)? second, whether the basic consideration in determining the decision-making to the cause of disparity in the criminal case of trafficking in persons (Trafficking)? Based on the results of research and discussion it can be concluded by the authors, namely: Disparities Punishment In Case Crime of Trafficking in Persons (Trafficking) to be subject to the fore on the cases into the public spotlight or the value of the losses inflicted major factors causing the disparity criminal can juridical terms of theoretical and empirical terms. In terms of theoretical juridical, criminal disparity is due to the existence of freedom and independence of the judge in the 1945 Constitution and the Law on Judicial Power shall exist, the ratio decidendi theory, theory and doctrine of res dissenting opinion pro veritate judicate hebetur. In terms of empirical considerations include the state of the defendant's personality, the social, economic, and public attitudes, as well as in the proof of the facts in the trial can also affect consideration of the judge. The judge himself should not be cut off in indecision and the principle of in dubio proreo, so it appears a criminal disparity. Rationale Judge In Decision Making Up Cause Determination Disparities existence Punishment In Case Crime of Trafficking in Persons (Trafficking). Judicial independence is also a factor of disparity. In Indonesia the principle of independence of judges (judicial discretionary power) is fully guaranteed in Article 1 of Law No. 48 Year 2009 concerning Judicial Authority.